Model Transpor Penyebaran Sampah di Teluk Jakarta - Setiawan, Agus; Riyadi, Agung (Jurnal Hidrosfir Indonesia, 2007)
Spreading of wastes from 11 river mouths around the Jakarta Bay during the east and west monsoons is simulated in this study, making use of transport model. The data of wastes weight and concentration used in this study are obtained from “Marine and Jakarta Bay Wastes Prevention” pilot project conducted by the government of DKI Jakarta. In this simulation, it is assumed that the weight of daily outflow of wastes is constant and the composition of wastes is not taken into account.From the simulation results there are found that during the west monsoon, wastes in the Jakarta Bay mostly transported eastward, spread until 3 km and accumulated in the eastern part of the Jakarta Bay. Wastes with concentration more than 10 kg/L spread out to the offshore until 1 km from the shore line or river mouth. On the other hand, the wastes mostly transported westward during the east monsoon. These wastes spread westward until 5 km and mix with the wastes from the river mouths which are located in the western part of the Jakarta Bay. The amount of wastes which are spread westward during the east monsoon is greater than the amount of wastes which are spread eastward during the west monsoon.Keywords: Jakarta Bay, wastes, transport model